Perspectiva dialógica no processo de educação em saúde veterinária - Manzi, Marcela de Pinho [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
A medicina veterinária, além de atuar diretamente na sanidade animal, age também na saúde humana, por meio de atividades de inspeção sanitária de alimentos, vigilância epidemiológica, sanitária e ambiental, atividades de orientação e educação em saúde no que diz respeito à saúde pública e zoonoses. Dentre as diversas zoonoses, algumas são mais frequentes em pequenas propriedades rurais de bovinocultura leiteira, devido às condições ambientais e de manejo favoráveis aos agentes etiológicos e vetores, além do acesso limitado à informação técnica acerca da medicina veterinária preventiva. O presente trabalho teve por objetivos analisar a realidade local de propriedades rurais bem como os métodos de educação em saúde (tradicional e dialógico), bem como propor uma nova perspectiva na educação em saúde veterinária. Foram envolvidas 37 pequenas propriedades rurais no interior do estado de São Paulo. Os dados foram obtidos por meio de aplicação de questionário, observação e prática de atividades de educação em saúde, no modelo dialógico. Primeiramente, observou-se grande distanciamento dos produtores frente ao médico veterinário, relacionando a imagem do profissional à fiscalização, acarretando em baixa adesão. O questionário indicou perfil de baixa produção, baixa tecnificação e baixa especialização, bem como deficiência com relação as medidas preventivas contra doenças zoonóticas. Quanto às atividades educativas, não houve adesão nas práticas tradicionais. No entanto as atividades dialógicas mostraram-se efetivas, com grande interesse e participação dos produtores. Conclui-se pela necessidade de mudanças nas práticas de educação em saúde no âmbito da medicina veterinária, usando da diversidade cultural entre meios acadêmico e rural como recurso a ser explorado, e a valorização da pluralidade dos saberes como fator determinante na interação produtor/veterinário.

Veterinary Medicine acts directly on the animal health and also on human health through activities of sanitary inspection of food, epidemiological surveillance, health and environmental measures of guidance and education in public health concerns and zoonoses. Among various zoonoses some are more frequently observed in small properties of dairy farming, due to favorable environmental and handling conditions for agents etiological and vectors as well as limited access to information. The lack of knowledge about these diseases by the rural population, where technical information is more scarce or deficient, alert to the need for accessibility to this technical knowledge addressed in a diversified, respectful and effective way. This work has an objective aims to analyze the local reality of rural properties as well as the methods of health education (traditional and dialogical), as well as propose a new perspective in veterinary health education. Small farms were used in the interior of the state of São Paulo. The data were obtained by means of a questionnaire, observation, and practice of health education activities, in both methods of health education afore mentioned. Firstly, there was a great distance from the producers in relation to the veterinarian, relating the image of the professional to the inspection, resulting in low adherence. The questionnaire indicated a low production, technification and specialization profile, as little attention well as low rates of preventive measures against zoonotic diseases. Regarding educational activities, there was no adherence to traditional practices. In contrast, the dialogical activities were effective, with great interest and participation of the producers involved. It is concluded that it is necessary to change health education practices in veterinary medicine, using the cultural diversity between the academic and rural ways as a resource to be explored and the valorization of both knowledge as a determining factor in the producer / veterinarian interaction.
Dialogical perspective in the process of health education veterinary
Keywords: Profilaxia de doenças; Bovinos; Educação; Mastite; Prophylaxis of diseases; Cattle; Mastitis; Education